Korelasi Pola Makan dan Aktivitas Fisik dengan Derajat Dismenore Primer pada Remaja Putri - Priska Meilinda Priardhana; Ardhiles Wahyu Kurniawan; Rif’atul Fani (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Adolescent girls represent a population that commonly experiences primary dysmenorrhea. Inadequate dietary habits may contribute to inflammatory responses, while low levels of physical activity can reduce the body’s natural pain regulation, both of which may intensify menstrual pain. This study aimed to analyze the association between dietary habits and physical activity with the severity of primary dysmenorrhea among adolescent girls. A quantitative correlational study with a cross-sectional design was conducted. Participants were selected using proportional random sampling, involving 71 eleventh-grade students at SMAN 6 Malang. Dietary intake was assessed using a FFQ, physical activity levels were measured through the PAL indicator, and dysmenorrhea severity was evaluated using the WaLIDD score. The results showed that nearly half of the respondents had adequate dietary habits (49.3%) and moderate physical activity levels (47.9%), while most participants experienced moderate primary dysmenorrhea (53.5%). Statistical analysis using Somers’ d and Gamma tests yielded p-values of 0.039 and <0.001, indicating significant associations between dietary habits, physical activity, and dysmenorrhea severity. Correlation analysis demonstrated a moderate inverse relationship between dietary habits and dysmenorrhea severity (r = −0.301) and a strong association between physical activity and dysmenorrhea severity (r = 0.690).